Prevention of fever and gram negative infection after open heart surgery by antiendotoxin. Issue 11 (November 1985) - Freeman, R; Gould, F K
Abstract : Naturally occurring preoperative antibody to enteric Gram negative bacilli (Escherichia coli agglutinins or antiendotoxin, or both) in 30 patients who had had open heart surgery was associated with a significantly lower incidence of early postoperative fever and postoperative Gram negative infection than occurred in 56 patients without preoperative antibodies. The protective effect was shown to be associated with antiendotoxin rather than antibody to the somatic antigen of the bacteria. Active or passive immunisation of patients having open heart surgery against endotoxin is likely to decrease significantly the morbidity after cardiopulmonary bypass.